Postcovid Guillain-Barré syndrome with severe course - case series two patients including clinical evaluation of smell and examination of olfactory event-related potentials (OERPs) - Pastorkova, Nikola; Janouskova, Karla; Vasina, Libor; Schulz, Helene; Astl, Jaromir; Holy, Richard (Biomedical papers, 2024)
Introduction. We report a case series two patients of Guillain-Barré syndrome (GBS) associated with previous COVID-19 that both patients survived. GBS is an immune-mediated disease that affects peripheral nerves and can cause life-threatening complications. Case Reports. In both cases (53-year-old female and 59-year-old male) with severe GBS with complications, the smell of sense was investigated subjectively using Sniffin' sticks identification tests and objectively using objective olfactometry by the evaluation of olfactory event-related potentials (OERPs). Both patients had good results of the subjective Sniffin' sticks identification test without patholgical findings. Results of objective examination of OERPs: the P2-N1 wave complex was equipotent. No olfactory disturbance could be detected in either case, OERPs were plentiful in both cases. Conclusion. The presentation of a case series two patients of post-covid GBS are an example of one of the many complications of COVID-19 that can cause prolonged recovery. Despite the severe course of GBS and the long recovery time, both patients returned to normal life. An expanded prospective study is planned for the future to investigate post-covid olfactory impairment. The prevalence of GBS associated with COVID-19 is still unknown but it is evident that both mild and severe forms of GBS have been described in patients.
Keywords: Guillain-Barré syndrome; COVID-19 infection; Sniffin stick tests; olfactory event-related potentials; objective olfactometry